The effects of accentuated eccentric loading on mechanical variables and agonist electromyography during the bench press - Castro, A. H.; Zangakis, D.; Moir, G. L. (Sports, 2020)
We compared the effects of accentuated eccentric loading (AEL) on mechanical variables and agonist muscle activation using low (30% 1-repetition maximum (1RM)) and high (80% 1RM) upward-phase loading with AEL (100% 1RM during downward phase) to traditional loading schemes (T) in the bench press. Twelve resistance-trained men (26 ± 6 years; 1RM: 134 ± 33 kg) performed sets of two repetitions with three-minute intervals using loading schemes of 30AEL, 30T, 80AEL, and 80T. AEL was applied using weight releasers while force plates and a 3D motion-analysis system were used to measure mechanical variables. Electromyographic activity of the pectoralis major and triceps brachii muscles was also recorded. The greater downward-phase loads experienced during the AEL conditions allowed greater overall mean vertical forces (mean difference ( x ¯ Diff): 118 N, p < 0.001), greater work ( x ¯ Diff: 43 J, p < 0.001), and greater pectoralis major muscle activation ( x ¯ Diff: 27 µV, p = 0.002) compared to the corresponding traditional loading schemes. However, there was little evidence of potentiation of the mechanical variables or muscle activity during the subsequent upward phases caused by the AEL schemes. It is possible that the use of weight releasers may disrupt lifting technique particularly during low AEL schemes thereby diminishing any benefits.